ENCHANTED WITH THE CITY OF THE SOUTH – NEW ORLEANS IN LAFCADIO HEARN’S LITERARY NONFICTION - Przeszlakowska-Wasilewska, Joanna (Acta Neophilologica, 2018)
This paper is devoted to the New Orleans stage in the writings of the nineteenth-century American literary journalist, Lafcadio Hearn. The major focus is on the writer’s fascination with the city’s unique Southern character which was skillfully grasped and conveyed by Hearn during the decade of his residence in New Orleans. The articles published in the Cincinnati Commercial and the Daily City Item are discussed in terms of the author’s sensual and emotional approach towards what he considered as the greatest assets of New Orleans: its tropicality, the Creole element, the climate, and the women. Special attention is paid to Hearn’s sensitivity to feminine beauty as the crucial determinant of the city image he managed to describe for future generations.